Outdoor learning in the school grounds: a study of proposed additional outdoor classrooms for primary schools in Kuala Lumpur Malaysia - Mohd. Yaman, Maheran; Abdullah, Fadzidah; Hj. Baharuddin, Zainul Mukrim; Othman, Rashidi; Mohd. Hussain, Mohd. Ramzi (2015)
This study is about opportunities for the use of outdoor classrooms in tropical climates, such as Kuala Lumpur in Malaysia. It investigates the possible advantages of teaching and learning school subjects at primary level, in outdoor classrooms in Malaysia, using the outdoor environment to improve student comfort levels and to provide enhanced learning opportunities. Preliminary investigations of hypothetical post occupancy evaluations and thermal comfort studies have shown positive results for outdoor classrooms in ‘heat island’ urban areas such as Kuala Lumpur. The paper also considers the economic benefits of reduced building costs.